Micropropagation of some Malaysian banana and plantain (Musa sp.) cultivars using male flowers - Darvari, Fatemeh Mahdavi; Meon, Sariah; Abdullah, Mohd Puad; Mahmood, Maziah (Academic Journals, 2010)
Male inflorescences have potential to be used as explants for rapid micropropagation of Musa sp. The male flowers of four banana cultivars, namely ‘Berangan’, ‘Rastali’, ‘Nangka’ and ‘Abu’ belonging to three genome types in Musa(AAA, AAB, and ABB), were cultured onto Murashige and Skoog (MS) medium which was supplemented with 1 mg/L of TDZ, BAP, Kin, 2-ip and Zea. The number of shoots was found to significantly increase in both TDZ and BAP treatments, as compared to other cytokinins. TDZ at 0.4, 0.6 and 0.8 mg/L, in particular, appeared to be optimum for shoot induction in ‘Berangan-AAA’, ‘Rastali-AAB’ and ‘Nangka-AAB’ and ‘Abu-ABB’, respectively. However, all the cultivars showed their highest response to regeneration at 8 mg/L of BAP. After the initiation of the explants onto the MS media for all the cultivars, the highest number of cauliflower-like bodies’ (CLBs) clusters was observed at two months of culture. The number of induced ‘CLBs’ cluster is dependent on the size of male buds. Male inflorescences with the size of 20 mm were found to induce more ‘CLBs’ clusters. Meanwhile, the number of shoots produced is dependent on both the cytokinins and cultivars used.